2021
DOI: 10.1177/15589250211000337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic glycosylation on the structure and properties of wheat gluten protein fibers

Abstract: Wheat gluten proteins are good raw materials for preparing fibers due to their excellent viscoelasticity. However, protein fibers made directly from wheat gluten have poor mechanical properties. In this paper, transglutaminase was used to induce the glycosylation reaction between wheat gluten proteins and carboxymethyl chitosan. The glycated proteins were then made into fibers by wet spinning. After glycosylation modification, the breaking strength and breaking elongation of the wheat gluten protein fibers (WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The pH group showed broader absorption peak in the 3,600-3,300 cm − 1 regions, indicating higher levels of -OH and -NH 2 groups. According to previous studies (Lei & Ma, 2021), all treatment groups showed a more pronounced absorption peak at 2,364 cm − 1 , which was attributed to NH 2 stretching vibrations. The absorption peak of the control group was much sharper, resulting that WGP had a high denaturation temperature (Fig.…”
Section: Ft-irsupporting
confidence: 68%
See 1 more Smart Citation
“…The pH group showed broader absorption peak in the 3,600-3,300 cm − 1 regions, indicating higher levels of -OH and -NH 2 groups. According to previous studies (Lei & Ma, 2021), all treatment groups showed a more pronounced absorption peak at 2,364 cm − 1 , which was attributed to NH 2 stretching vibrations. The absorption peak of the control group was much sharper, resulting that WGP had a high denaturation temperature (Fig.…”
Section: Ft-irsupporting
confidence: 68%
“…Enzymatic treatment (ET): The ET was based on the method of Lei et al with minor modi cations (Lei, & Ma, 2021). The 1% WGP (W/V) was dissolved in deionized water stirred for 0.5 h, after adding 20 U/g of TGase (transglutaminase), the solution was placed in a water bath (40°C) and shaked at 110 r/min for 24 h. After that, the suspension was cooled in an ice-water bath to inhibit enzyme activity.…”
Section: Ph-shifting Acetic Acid and Enzymatic Treatmentmentioning
confidence: 99%
“…Heating to 121 °C denatured all LF in both milk samples within 4 s [ 176 ]. Additionally, it has been reported that a protein’s glycosylation patterns may influence its thermal stability [ 177 ]. Specifically, in the case of LF, glycosylation at Asn281 shields bovine lactoferrin from trypsin cleavage at Lys282, whereas the glycosylation of human lactoferrin does not offer similar protection [ 178 ].…”
Section: Limitation Of Lactoferrin Lactoferrin Analogues and Future P...mentioning
confidence: 99%
“…These films could be significantly improved, serving as potential candidates for high-watercontent food packaging. 119 The addition of TGase to whey protein-polycarboxymethyl chitosan to prepare composite membranes greatly improved the stretching of plastics and could potentially prevent environmental pollution problems. TGase markedly promoted the stretching ability of WPC plastics, with elongation increasing from 7.3% to 31.3% due to TGase treatment.…”
Section: Applications Of Enzyme-prepared Hydrogelsmentioning
confidence: 99%
“…TGase and zinc have been used to prepare gelatin hydrogel films, which were insoluble and permeable, with suitable mechanical properties. These films could be significantly improved, serving as potential candidates for high-water-content food packaging . The addition of TGase to whey protein-poly­carboxy­methyl chitosan to prepare composite membranes greatly improved the stretching of plastics and could potentially prevent environmental pollution problems.…”
Section: Applications Of Enzyme-prepared Hydrogelsmentioning
confidence: 99%